Muscle Power during Standing and Seated Trunk Rotations with Different Weights - Erika Zemková; Michal Jeleň; Ludmila Zapletalová; Dusan Hamar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
This study compares peak and mean power during standing and seated trunk rotations with different weights. Twenty seven fit men completed four trials of trunk rotations in both standing and seated positions with a bar weight of 5.5, 10.5, 15.5, and 20 kg placed on the shoulders. The FiTRO Torso Premium was used to monitor basic biomechanical parameters throughout the movement. Results showed significantly higher peak power during standing than seated trunk rotations at weights of 20 kg (274.4±63.5 vs. 206.4±54.6 W, p=0.004), 15.5 kg (371.2±93.9 vs. 313.5±72.3 W, p=0.007), and 10.5 kg (336.9±77.8 vs. 286.3±66.0 W, p=0.009) but not at 5.5 kg (191.6±46.2 vs. 166.0±37.0 W, p=0.061). Similarly, mean power in the acceleration phase of trunk rotations was significantly higher when performed in standing than seated position at weights of 20 kg (143.2±32.1 vs. 101.9±23.7 W, p=0.008), 15.5 kg (185.1±42.3 vs. 150.4±36.5 W, p=0.019), and 10.5 kg (169.8±40.7 vs. 139.7±31.6 W, p=0.024) but not at 5.5 kg (107.4±29.4 vs. 86.5±21.1 W, p=0.111). Furthermore, peak and mean power during standing trunk rotations significantly correlated with values achieved in the seated position at the weight of 5.5 kg (r=0.684, p=0.027; r=0.676, p=0.033) but not at 10.5 kg (r=0.589, p=0.089; r=0.552, p=0.143), 15.5 kg (r=0.493, p=0.243; r=0.436, p=0.298), and 20 kg (r=0.357, p=0.361; r=0.333, p=0.417). In conclusion, power production is greater during standing as compared to seated trunk rotations, with more pronounced differences at higher weights. This fact has to be taken into account when training and testing the trunk rotational power.